PLTS Utilization of Solar Power for Irrigation of "Nyayur" - Yasa, I Made Sumerta; Saputra, I Gusti Ngurah Agung Dwijaya; Elfarosa, Ketut Vini; Indrayanti, Anak Agung Putri; Sugirianta, Ida Bagus Ketut; Putrawan, Agus Adi (Jurnal Pengabdian Masyarakat, 2024)
Purpose: Around 10 hectares of rice fields, including nyayur land, in Subak Sembung Peguyangan, North Denpasar, Bali, do not receive water, especially in the dry season, due to the location of the land being higher than the main irrigation canal. For this reason, it is necessary to create water irrigation by installing a 125W/220V water pump with an electricity supply from solar power. Method: The stages of implementing the service are carried out with the stages of socialization, installation and testing of tools/systems, training and maintenance of tools/systems. Practical Applications: With the installation of solar panels (PLTS) along with water pumps, it is hoped that it will be able to overcome the water shortage, so that it is easier for vegetable farmers to get water to water their vegetable crops. Likewise, Subak members are expected to gain new knowledge about renewable energy. Conclusion: After carrying out community service, especially members of the Sembung Subak, the results were obtained in the form of installing a PLTS unit with a water pump, making it easier to water vegetable and flower plants which previously had to carry water from far away but now just by turning on the water pump and water faucet, you can directly water the surrounding area. 31,400 m2.